Guaranization, mixed blood and non-humans. Notes not to delimit the «Guaraní» in Jujuy’s Ramal (Argentinian Norwest) - Sarra, Sonia Elizabeth (2020)
This paper explores human and non-human forms of Guarani sociality  in the multiethnic region of the Ramal in Jujuy (Argentinian Norwest). Specifically, it aims to show the fluidity of socio-ethnic limits that distinguish what is Guarani from what is not, and the porosity of ontological limits that differentiate humans from nonhumans.   argue that there are two Guarani excesses in the region, which make it difficult to classify and define Guarani borders. The first one is sociological in strict sense and refers to the impossibility f delimiting the Guarani identity within communities’ borders and persons who explicitly identify themselves as «Guarani». It is necessary to expand the «Guarani» towards the local guaranized population of mixed blood. The second excess is ontological and refers to the expansion of social ties towards non-human worlds where Guarani ancestors, who become forest owners, live.